Keanekaragaman Aves Di Kawasan Cagar Alam Pulau Dua - Meliyana; Rohmalia Hayatun Nufus; Resty Apriani; Juhaeriyah Juhaeriyah; An Nur Dwikanira Niswara (Universitas Nusantara PGRI Kediri, 2024)
The second island sanctuary is a bird's paradise, especially water birds. In the 2018 report on banten province's environmental service, at least 110 birds from 39 different tribes, including more than 57 categorized water birds, of which 38 are protected in Indonesia. The purpose of the study is to identify the diversity of aves found in the two-island wildlife sanctuary in the province of banten, in precisely the noble rice village, sub-district, and attack. The method of exploration is used in data collection used line transect techniques. Studies have found 12 species from 9 families caught by both the eye and the binoculars. The ardeidae family dominates much of the cruising area because of its natural habitat that is close to the waters in which it can easily feed. Small egrets roamed the mangrove vegetation while egrets roamed along the coast. There are 10 species of birds with lc conservation status as well as 1 with the vu conservation status of acridotheres javanicus and en, the mycterea cinereal.